Rijndael encryption technique: authentication for computer application - Hamid Ali, Firkhan Ali; Mohd Sukri, Mohd Khairul Amin; Mohamad, Md Syukri (journalsweb.org, 2020)
Password Management System is used for file protection and encryption file process can be done in computer application especially through the cloud computing environment. This approach has been adapted or implemented in various managements to secure application in computing. This system functions to help the application computing users to protect information using priority password without having difficulty. The system had done for protection system information process. An activation to encrypt files to increase the best and systematic services to the organization management in application computing. After all, the result was reached the goals that punctual the file protection to encrypt file through cloud computing environment.